Malicious URL Detection Algorithm based on BM Pattern Matching - Yu, Fuqiang (International Journal of Security and Its Applications, 2015)
In the virus world of Internet, it is a challenging and urgent problem that how can we ensure the safety of search engines. A security subsystem of the search engine based on the research of content-based image search engine system V2.0 is developed. A malicious URL (Uniform Resource Locator) detection method based on BM (Boyer-Moore) pattern matching is proposed. The main research contents and results are as follows: Many malicious URLs could be downloaded by web image search, which may cause unnecessary loses to the users. So the malicious URL detection algorithm based on BM pattern matching is proposed. This method is to let the URL source code match the virus characteristics in the database to confirm whether the URL is safe or not. Web image search detects 203 malicious URLs based on this method. By kaspersky scanning, we confirmed 189 URLs to be malicious URLs, and the error rate is 6.9%, and the accurate rate is 93.1%. The experimental results show that the malicious URL detection algorithm provides secure URLs for web image search engine..